Development of an occupational advice intervention for patients undergoing lower limb arthroplasty (the OPAL study) - Baker, Paul; Coole, Carol; Drummond, Avril E.R.; McDaid, Catriona; Khan, Sayeed; Thomson, Louise; Hewitt, Catherine; McNamara, Iain; McDonald, David; Fitch, Judith; Rangan, Amar (Biomed Central, 2018)
Background: There are an increasing number of patients of working age undergoing hip and knee replacements. Currently there is variation in the advice and support given about sickness absence, recovery to usual activities and return to work after these procedures.